Motivation of Santri Identity in Figures of Spiritual Nursing Implementation in Students Who Will Undergo Clinical Practice - Suhartini, Titik (UNUSA Press, 2025)
Hafshawaty University is one of the educational institutions that is concerned with graduates who are santri, therefore nursing students who study at Hafshawaty University are expected to become santri nurses; namely nurses who have high spiritual care forpatients. Because in addition to getting a lot of Islamic spiritual knowledge in Islamic boarding schools, Hafshawaty University students also get additional spiritual care knowledge in local Islamic contexts that can be applied to meet the spiritual needs of patients in hospitals. Departing from this reason, the author feels that Hafshawaty University students need to increase their awareness as santri nurses, who have advantages in carrying out spiritual nursing. So that increasing awareness as students also needs to be motivatedThe target of this community service is to increase motivation and awareness as students and nursing students who can meet the spiritual needs of patients.This community service is carried out in the form of counseling for students who will carry out clinical practice in hospitals, education and training on procedures forconducting assessments to spiritual-based nursing care. The program is planned to be carried out during the briefing before the practice so that it can be attached andimplemented during the implementation of clinical practice in the Hospital.